The Effectiveness and Legal Certainty of ETLE Sanctions in Indramayu in the Context of Vehicle Constraints That Have Not Changed Their Name - Aldi Ferdiansyah; Waluyadi Waluyadi; Gunadi Rasta (Riviera Publishing, 2026)
The implementation of Electronic Traffic Law Enforcement (ETLE) has become an important innovation in improving transparency, efficiency, and accountability in traffic law enforcement. However, the effectiveness of ETLE implementation still faces challenges related to legal certainty, particularly concerning vehicles that have undergone ownership transfers but have not completed administrative name changes. This condition may result in sanctions being imposed on previous vehicle owners who are not the actual perpetrators of traffic violations, potentially creating injustice in the law enforcement process. This study aims to analyze the effectiveness and legal certainty of ETLE sanctions in Indramayu Regency, including the legal basis, implementation mechanisms, and factors that hinder the enforcement process. This research employed a qualitative method with an empirical juridical approach. Data were collected through legal document analysis, observations at the Indramayu Police Traffic Unit, interviews with ETLE officers, and questionnaires distributed to road users. The results showed that ETLE implementation has improved the efficiency of traffic law enforcement, reduced direct interactions between officers and traffic violators, and increased transparency through the use of electronic evidence. However, legal certainty has not been fully achieved due to inaccurate vehicle ownership data, technical limitations in license plate recognition, limited camera coverage, and low public understanding of ETLE procedures. In conclusion, ETLE provides significant benefits for modern traffic law enforcement; however, improvements in vehicle administration systems, technological infrastructure, and public legal awareness are required to ensure that sanctions are imposed fairly, accurately, and in accordance with applicable legal principles.